The Use of Arabic Podcasts Integrated with Motivation to Learn in Improving Students’ Arabic Speaking Skills - Annisa Mutiara Putri Effendy; Haeruddin Haeruddin; Ilham Ramadhan; Muhammad Anwar Bin Ahmad (JOLLT Journal of Languages and Language Teaching, 2026)
The advancement of digital technology has transformed language learning media, with podcasts emerging as an alternative platform to enhance speaking skills. This study investigates the use of Arabic podcasts integrated with strong motivation to learn in improving students’ Arabic speaking skills (maharah al-kalam). The study applies a qualitative case study approach. Data were gathered through open-ended questionnaires and in-depth interviews with students actively engaging with Arabic-language podcast content. The data were analyzed using the Miles and Huberman model, including data reduction, display, and conclusion drawing. The findings reveal that podcasts significantly support the development of speaking fluency, vocabulary acquisition, pronunciation accuracy, and learner confidence in oral communication. Exposure to authentic and contextual input through podcasts facilitates meaningful learning experiences while promoting flexible and independent learning strategies. These outcomes reinforce the theoretical relevance of Communicative Language Teaching and Second Language Acquisition frameworks within Arabic language instruction supported by digital audio media. Importantly, this study addresses a gap in Arabic language pedagogy, as previous research has largely concentrated on EFL or younger learners, leaving higher education contexts underexplored. By situating Arabic podcasts within a university setting, the study provides empirical evidence for their role as an innovative alternative to enhance speaking proficiency. The study further recommends that educators incorporate podcasts into classroom practices, curriculum design, and independent learning activities to optimize student engagement and outcomes. It also opens pedagogical opportunities for integrating podcasts as an instructional strategy in higher education and calls for further research on their long-term impact on other language competencies.